Behavioural genetics of suicidality in bipolar disorder: The interaction between clock and 5-HTT polymorphisms and early life stress. (30th December 2016) - Poletti, S.; Riccaboni, R.; Pirovano, A.; Lorenzi, C.; Locatelli, C.; Colombo, C.; Benedetti, F.
Highlights: ● CLOCK and 5-HTTLPR modulated the relationship between early stress and suicide. ● The effect of CLOCK overcomes the influence of 5-HTTLPR. ● In C carriers higher early stress associates to the likelihood of attempting suicide. ● A positive relationship exists between suicide and early stress in l/l-C carriers. ● In the l/l-T/T group suicidality is not related to the amount of childhood stress.